Analysing the spatial pattern of road networks in Kimberley, South Africa - Kabanda, Tabaro (Town and Regional Planning, 2023)
The increasing burden on South African road networks necessitates sustainable solutions that conclude their spatial configuration and arrangement. A deeper understanding of the existing road network’s spatial organisation is, therefore, required. This study evaluates the structural design of road networks in Kimberley, South Africa, using spatial network science and open-source OpenStreetMap data. Nonplanar-directed multigraphs for Kimberley are constructed to analyse the structural and morphological characteristics of the network. The study area was evaluated with several network-analysis methods such as completeness, degree of centrality, betweenness, closeness, and PageRank. The study found that Kimberley has a low degree of centrality of 0.00111. This indicates that the road network should be less congested because there are fewer vulnerable spots. Because of the availability of two-way streets, the total edge length in the Kimberley network is nearly double the total street length. There are 2.97 streets radiating from Kimberley nodes on average. This suggests that three-way intersections are prevalent in Kimberley. Centrality measures and analysing the effects in terms of accessibility to the commerce and services of the city show how the legacy of racial segregation, poverty, and isolation from social and economic opportunities impedes the places within Kimberley. Results from the study also indicate that the informal sections of Galeshewe are fine-grained in terms of road network, while Kimberley CBD and nearby districts have coarse grain roads. This pattern contributes to the relative overall low average street segment length (a proxy for block size) of 107 metres in Kimberley.